Everyday Active Citizenship the Balkan Way: Local Civil Society and the Practice of 'Bridge Building' in Two Post-Yugoslav Cities - Goldstein, Piotr (Peter Lang, 2016)
Active citizenship in the post-war Western Balkans has traditionally been studied in the context of either Western-style (and usually foreign-funded) Non-Governmental Organisations (NGOs) or, more recently, protest movements. This chapter highlights a wider range of better- and lesser-known forms of civil society in the contemporary post- Yugoslav space. It shows how interest associations, student unions, religious groups and online communities can all contribute to vibrant civil society, even if their work seems distant from the post-war area’s current problems. This civil society, the chapter argues, creates an environment in which the people of the western Balkans can enact their citizenship and, little by little, ‘build bridges’, across ethnic lines and beyond.
Cartographies of Differences: Interdisciplinary Perspectives
Keywords: Post-Yugoslav; Civil society; Active Citizenship; Balkans; Non-governmental organisations